Pengaruh Bermain Peran Terhadap Perkembangan Sosial Anak Usia Dini - Fredericksen Victoranto Amseke; Marni Taneo (FKIP UNSULTRA, 2025)
Social development is very important for early childhood. One learning method to stimulate children's social development is the role playing method. Role playing is a strength that is the basis for the development of creativity, memory stages, group cooperation, vocabulary absorption, the concept of family relationships, self-control, special skills, affection and cognitive skills. This research aims to determine the effect of role playing on the social development of children aged 5-6 years in Kuanino Village, Kupang City. This research uses quantitative methods. The data collection tool uses a psychological scale with role playing scale instruments and Child Social Development Scale instruments. The respondents for this research were 73 children aged 5 - 6 years using total sampling techniques in three PAUDs in Kuanino Village, Kupang City. The data analysis technique uses simple linear regression analysis. The results of this study prove that role playing has a positive and significant effect on the social development of children aged 5 - 6 years by 11.3%. It is hoped that educators can stimulate children with role-playing methods so that they can improve the social development of early childhood.